1990
DOI: 10.1039/ft9908603321
|View full text |Cite
|
Sign up to set email alerts
|

Electron paramagnetic resonance study of the reaction of ground-state aluminium atoms with a series of ethers in a rotating cryostat

Abstract: Ground-state Al atoms react with symmetric cyclic and acyclic ethers at 77 K in a rotating cryostat to give a host of mononuclear organoaluminium compounds. Magnetic parameters determined from EPR spectra given by Al atoms and acyclic ethers are consistent with the formation of novel C-C and C-H aluminium atom insertion products. A third species has been tentatively assigned to the product given by Al atom insertion into the C-0 bond. In addition a carboncentred radical is formed by loss of a hydrogen atom fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
46
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 17 publications
2
46
0
Order By: Relevance
“…For reactions between Al/Al ϩ and O͑CH 3 ) 2 , Parnis et al 11 obtained the binding energy of Al-O͑CH 3 ) 2 through temperature dependence measurements of reaction equilibrium constants, and Bouchard et al 12 measured the binding energy of Al ϩ -O͑CH 3 ) 2 using laserablation high-pressure mass spectrometry. The formation of the Al association complex as well as insertion products was revealed by Chenier et al electron paramagnetic resonance 13 ͑EPR͒ and Kasai electron spin resonance 14 ͑ESR͒ measurements and Sakai 15 and Fänström et al 16 theoretical predictions. For transition metals, Burnier et al 17 showed the formation of Fe ϩ -(CH 2 O) by ion cyclotron resonance mass spectrometric measurements of the Fe ϩ reaction with dimethyl ether, whereas Pedersen et al 18 identified the association complex of Zr-O͑CH 3 ) 2 in a combined spectroscopic, kinetic, and theoretical study.…”
Section: Introductionmentioning
confidence: 91%
“…For reactions between Al/Al ϩ and O͑CH 3 ) 2 , Parnis et al 11 obtained the binding energy of Al-O͑CH 3 ) 2 through temperature dependence measurements of reaction equilibrium constants, and Bouchard et al 12 measured the binding energy of Al ϩ -O͑CH 3 ) 2 using laserablation high-pressure mass spectrometry. The formation of the Al association complex as well as insertion products was revealed by Chenier et al electron paramagnetic resonance 13 ͑EPR͒ and Kasai electron spin resonance 14 ͑ESR͒ measurements and Sakai 15 and Fänström et al 16 theoretical predictions. For transition metals, Burnier et al 17 showed the formation of Fe ϩ -(CH 2 O) by ion cyclotron resonance mass spectrometric measurements of the Fe ϩ reaction with dimethyl ether, whereas Pedersen et al 18 identified the association complex of Zr-O͑CH 3 ) 2 in a combined spectroscopic, kinetic, and theoretical study.…”
Section: Introductionmentioning
confidence: 91%
“…These insertion products have been identiÐed by EPR spectroscopy and the isotropic hydrogen and aluminium hyperÐne interactions (hÐ) were found to increase as the electron-withdrawing ability of the groups attached to aluminium increases. Aluminium atoms have also been shown to insert into the CÈH, CÈC and CÈO bonds of symmetric cyclic and acyclic ethers5, 6 .2 isotopically substituted precursors are not always available to conÐrm the proposed structures of these aluminium species.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Ground-state Al ( 2 P 1/2 ) atoms have been shown to activate a number of different types of bonds resulting in the formation of insertion products. Experiments involving NH 3 , 3,4 H 2 O, 5 H 2 S, H 2 Se, 6 CH 3 OCH 3 , 7,8 and CH 4 9 yielded HAlNH 2 , HAlOH, HAlSH, HAlSeH, CH 3 AlOCH 3 and CH 3 AlH, respectively, indicating that Al atoms can activate N-H, O-H, S-H, Se-H, C-O and C-H bonds. Al atoms have also been reported to activate the C-C bond of cyclohexanol, 10 1-methylcyclohexanol 10 and diethyl ether.…”
Section: Introductionmentioning
confidence: 98%
“…Al atoms have also been reported to activate the C-C bond of cyclohexanol, 10 1-methylcyclohexanol 10 and diethyl ether. 8,11 With respect to halogenated compounds, co-condensation of Al atoms with HCl in an Ar matrix resulted in the formation of HAlCl 12,13 at low concentration while increasing the HCl concentration to B8% yielded AlCl 2 . Finally, reaction of ground-state Al atoms with bromocyclopropane (CpBr) in adamantane at 77 K gave the two C-Br insertion products CpAl 79 Br and CpAl 81 Br as well as the allyl radical.…”
Section: Introductionmentioning
confidence: 99%